2021
DOI: 10.3390/w13081061
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Threshold for Flash Flood Warning Based on Model Output of Soil Moisture: Case Study Wernersbach, Germany

Abstract: Convective rainfall can cause dangerous flash floods within less than six hours. Thus, simple approaches are required for issuing quick warnings. The flash flood guidance (FFG) approach pre-calculates rainfall levels (thresholds) potentially causing critical water levels for a specific catchment. Afterwards, only rainfall and soil moisture information are required to issue warnings. This study applied the principle of FFG to the Wernersbach Catchment (Germany) with excellent data coverage using the BROOK90 wat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The locations of the case studies are shown in Figure 3. The majority of studies which were reviewed, were carried out in high-income regions within Europe (Montesarchio et al, 2015;Papagiannaki et al, 2015;Candela and Aronica, 2016;Forestieri et al, 2016;Santos and Fragoso, 2016;Bouwens et al, 2018;Hofmann and Schüttrumpf, 2020;Luong et al, 2021) and Asia (Jang, 2015;Wu et al, 2015;Miao et al, 2016;Liu et al, 2018;Zhai et al, 2018;Li et al, 2019). Few studies using RT for flash floods EWS were reported in America (Ávila et al, 2015;UNAL, 2018;Guerrero Hoyos and Aristizábal Giraldo, 2019;Castillo et al, 2020), and low-income countries in Africa (Young et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The locations of the case studies are shown in Figure 3. The majority of studies which were reviewed, were carried out in high-income regions within Europe (Montesarchio et al, 2015;Papagiannaki et al, 2015;Candela and Aronica, 2016;Forestieri et al, 2016;Santos and Fragoso, 2016;Bouwens et al, 2018;Hofmann and Schüttrumpf, 2020;Luong et al, 2021) and Asia (Jang, 2015;Wu et al, 2015;Miao et al, 2016;Liu et al, 2018;Zhai et al, 2018;Li et al, 2019). Few studies using RT for flash floods EWS were reported in America (Ávila et al, 2015;UNAL, 2018;Guerrero Hoyos and Aristizábal Giraldo, 2019;Castillo et al, 2020), and low-income countries in Africa (Young et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The hydrological methods are based on the concepts of the FFG approach, which was created by focusing on mountainous regions, uniform rainfall depth/duration over space and time and catchment sizes up to 1,000 km 2 (Mogil et al, 1978). The FFG has been modified to include gridded data (Schmidt et al, 2007;Gourley et al, 2012), synthetic hyetographs (Jang, 2015;Montesarchio et al, 2015;Wu et al, 2015;Candela and Aronica, 2016), distributed hydrological model (Jang, 2015;Miao et al, 2016;Zhai et al, 2018), and the dynamic condition of antecedent soil moisture (AMC) (Montesarchio et al, 2015;Luong et al, 2021). Gridded FFG have proposed to derive RT based on rainfall raster data, in order to capture spatial variability (Bae et al, 2018).…”
Section: Description Of the Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The sloping contours tended to hold water longer, thus increasing the likelihood of flooding, whereas steeper contours tended to displace water in lower elevation areas, thus flooding probability was low. The primary determining factor of flooding was the intensity of rainfall [51]. Furthermore, low river densities can also cause flooding.…”
Section: Multi-natural Hazard Analysismentioning
confidence: 99%
“…Moreover, the quantile method also aims to standardize parameter values with different units and measurement methods, ranging from 1-5 in the present analysis. The simple additive weighting (SAW) method, often used to complete multi-attribute decision-making [51], was employed here to combine each parameter and was calculated according to Equation (2):…”
Section: Multi-natural Hazard Analysismentioning
confidence: 99%